Penerapan Metode Card Sort Pada Pembelajaran Fiqh Materi Sholat Fardhu Untuk Meningkatkan Motivasi Belajar Siswa Kelas II MI Miftahul Ulum Cempokolimo - Niva Kurnia; Akhmad Fauzi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This article aims to increase the motivation to learn Fiqh for class II Miftahul Ulumu Cempoko Limo, in learning Fiqh using the Card Sort method. this article is a Classroom Action Research. The subjects of this study were 20 grade II students of Miftahul Ulumu Cempoko Limo. The results of the article showed that there was an increase from cycle I to cycle II. The implementation of fiqh learning using the Card Sort method in order to increase students' learning motivation is carried out with the following learning steps: (1) Studying the concept of a subject matter, (2) Matching the material on paper A to paper B, (3) Discussing the results of compiling , and (4) Group presentation in front of the class. The average cycle motivation results increased, the average in the first cycle was 70 increased to 83 in the second cycle and the results of the learning motivation questionnaire in the first cycle was 66% with the category once enough to 86% with the very good category in the second cycle. So it can be concluded that the use of the Card Sort method can increase students' learning motivation.